The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11999-011-1940-9
|View full text |Cite
|
Sign up to set email alerts
|

Single- versus Double-bundle ACL Reconstruction: Is There Any Difference in Stability and Function at 3-year Followup?

Abstract: Background Despite a number of studies comparing postoperative stability and function after anatomic doublebundle and single-bundle anterior cruciate ligament reconstruction (ACLR), it remains unclear whether double-bundle reconstruction improves stability or function. Questions/purposes We therefore asked whether patients having single-and double-bundle ACLR using semitendinosus (ST) alone differed with regard to (1) postoperative stability; (2) ROM; and (3) five functional scores. Methods We prospectively fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 47 publications
1
88
1
2
Order By: Relevance
“…Desai et al 20 Zhu et al 12 Kongtharvonskul et al 19 Li et al 18 (2013) Xu et al 13 Tiamklang et al 15 van Eck et al 14 Meredick et al 16 Gobbi, 2012 28 þ þ À À À þ À À À Hussein, 2012 29 À þ À À þ þ À À À Lee, 2012 30 À þ À À þ À À À À Nuñez, 2012 31 À À À À þ À À À À Ochiai, 2012 32 À À À À þ À À À À Lee, 2012 33 þ À À À À À À À À Suomalainen, 2012 34 À þ À À À À À À À Araki, 2011 35 À þ þ þ þ þ þ À À Fujita, 2011 36 þ þ þ À À þ À À À Hemmerich, 2011 37 À þ þ À þ À À À À Kyoung, 2011 38 þ À À À À À À À À Misonoo, 2011 39 À þ À þ À À þ À À Plaweski, 2011 40 À þ À À À À À À À Siebold, 2011 41 þ À À À À À À À À Stefani, 2011 42 þ À À À À À À À À Suomalainen, 2011 43 þ…”
Section: Discussionunclassified
“…Desai et al 20 Zhu et al 12 Kongtharvonskul et al 19 Li et al 18 (2013) Xu et al 13 Tiamklang et al 15 van Eck et al 14 Meredick et al 16 Gobbi, 2012 28 þ þ À À À þ À À À Hussein, 2012 29 À þ À À þ þ À À À Lee, 2012 30 À þ À À þ À À À À Nuñez, 2012 31 À À À À þ À À À À Ochiai, 2012 32 À À À À þ À À À À Lee, 2012 33 þ À À À À À À À À Suomalainen, 2012 34 À þ À À À À À À À Araki, 2011 35 À þ þ þ þ þ þ À À Fujita, 2011 36 þ þ þ À À þ À À À Hemmerich, 2011 37 À þ þ À þ À À À À Kyoung, 2011 38 þ À À À À À À À À Misonoo, 2011 39 À þ À þ À À þ À À Plaweski, 2011 40 À þ À À À À À À À Siebold, 2011 41 þ À À À À À À À À Stefani, 2011 42 þ À À À À À À À À Suomalainen, 2011 43 þ…”
Section: Discussionunclassified
“…The median sample size was 10 (range, [8][9][10][11][12][13][14] cases for in vitro studies and 30 (range, 21-90) cases for in vivo studies. The average age of subjects was 60.7 (median, 62; range, 31-72) years for in vitro studies and 28.6 (median, 29; range, 12-50) years for in vivo studies.…”
Section: Methodsmentioning
confidence: 99%
“…Using a manual PS test some clinical studies showed superior rotational laxity control of the knee after DB compared with SB ACL reconstruction [15,32,33,39], while other studies reported similar results in both techniques [10,27].…”
Section: Introductionmentioning
confidence: 97%
“…In addition, surgical techniques might not have been sufficiently developed yet as some recent studies did not show a significant clinical benefit between singlebundle ACL reconstruction technique and double-bundle ACL reconstruction technique [12,13].…”
Section: Discussionmentioning
confidence: 99%